(untitled) (Academic Journal of Internal Affairs, 2022)
Aim: This article, after a theoretical introduction, gives an overview of how health promotion has been implemented in the past years for the staff of the Police Headquarters of Szabolcs-Szatmár-Bereg County. In practice, how the attitude that human health is a value that should be appreciated and valued can be put into practice here at this end of Hungary. Methodology: We give a brief overview of the historical and theoretical background to our health promotion activities in general and regarding the police force. Then we move on to the presentation of our programmes being currently implemented. Findings: A systematic review of health promotion is important to the development and implementation of an appropriate health plan. It is to this aim that we present the national and the local police health promotion within the Malét-Szabó Activity Framework Modell. Value: Our review highlights how it is possible to develop a unique and complex health promotions system by the coordination of the personal, organizational and environmental factors.